IMPLEMENTATION OF PUBLIC SERVICE POLICIES IN THE OFFICE BIMA CITY WEIGHBRIDGE RETRIBUTION OFFICE - Muhammad Iptidayah; Taufik Irfadat (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
The purpose of this stuy is to determine the principle of public service in the office of the Bima City weighbridge retribution, the population of this study is 39 respondents consisting of leaders and, drivers, and traders / entrepreneurs, given the relatively small population and easy to reach population distribution, the sample of the population using random sampling so that the sample amounted to 30 respondents. Quantitative descriptive research is research that is used to analyze data by describing it. Quantitative descriptive is meant in this study, describes and describes and analyzes the answers from the sample that provides options for the answers provided in the form of a questionnaire. The results of this study are the responses of respondents, who said that 20 people or 51.28% answered accordingly, 12 people or 30.77% answered accordingly, 7 people or 17.95% who answered did not fit. or 0% For the simplicity of public service variables, which means that services are carried out in an easy, fast, precise, straightforward, straightforward manner, easily understood by the people who carry out services Keywords; Implementation, Retribution, Public Service